Codifying choice of law around the world : an international comparative analysis - Symeonides, Symeon, 1949- (New York : Oxford University Press, 2014)
This title chronicles, documents, and celebrates the extraordinary, massive country-by-country codification of Private International Law (PrIL) or Conflict of Laws that has taken place in the last 50 years from 1962-2012. The book provides a horizontal comparison and discussion of these codifications and conventions, firstly by comparing the way they resolve tort and contract conflicts, and then by comparing the answers of these codifications to the fundamental philosophical and methodological dilemmas of PrIL.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 20, 2014).
Keywords: Comparative law; Conflict of laws